FUNGSI PENGATURAN DAN MANFAAT PROGRAM JAMINAN SOSIAL TENAGA KERJA BAGI PEKERJA - Suhandi Suhandi (Perspektif, 2003)
In the purpose of providing protection on the work forces, then it is founded a social insurance program for employees that provide protection or assurance including on workplace accidents, health service insurance, death fund and retired fund. It is the responsibility of employers to support the employees to participate in Jamsostek program because the program basically is the right of employees to be the member of the program conducted by the Jamsostek Ltd.